Die Kronzeugenantragstellung bei Kartellen mit multi-jurisdiktionalen Auswirkungen - Triantafyllou, Argyro (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The use of leniency programmes appears to be less attractive in case of cartels with multi-jurisdictional effects. This book demonstrates that a cartelist who manages to be the first to submit a leniency application in one jurisdiction has no legal certainty of not being subject to sanctions in other jurisdictions. The measures undertaken so far by legislators to harmonize existing leniency programmes have not provided an adequate solution yet. In order to eliminate the prevailing problems in cases in which multiple leniency applications are required the author suggests alternative leniency models at EU and global level from which both potential leniency applicants and competition authorities may benefit.